2017
DOI: 10.1159/000477268
|View full text |Cite
|
Sign up to set email alerts
|

Colonic Histological Criteria Predict Development of Pouchitis after Ileal Pouch: Anal Anastomosis for Patients with Ulcerative Colitis

Abstract: Background/Aims: Pouchitis is one of the main complications after ileal pouch-anal anastomosis in patients with ulcerative colitis. The aim of this study was to determine whether the use of colonic histological criteria can predict the development of pouchitis. Methodology: We retrospectively reviewed 147 patients' clinical data and performed a histological evaluation of the resected total colon using Tanaka's criteria, which comprise the following 6 factors: ulceration (H1), crypt abscesses (H Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…In previous studies, attempts have been made to predict pouchitis using different parameters. These include genetic profiling, 30,31 perioperative characteristics, 32,33 and histological valuation, 34 most of which were with poor performance or underpowered. Another study identified increased proportions of Fusobacteriaceae and reduced proportions of Faecalibacterium in fecal samples of patients with pouch inflammation, but research focusing on the relationship between BT and pouchitis is still lacking.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, attempts have been made to predict pouchitis using different parameters. These include genetic profiling, 30,31 perioperative characteristics, 32,33 and histological valuation, 34 most of which were with poor performance or underpowered. Another study identified increased proportions of Fusobacteriaceae and reduced proportions of Faecalibacterium in fecal samples of patients with pouch inflammation, but research focusing on the relationship between BT and pouchitis is still lacking.…”
Section: Discussionmentioning
confidence: 99%
“…A BH22 light microscope (Olympus Corporation; magnification, ×400) was used to observe the histological damage and inflammation of the colon tissues. Severity of histological inflammation was graded as described previously (23,24): Ulceration (0, none; 1, erosion; 2, submucosa ulceration); crypt abscesses (0, none; 1, mild; 2, severe), degree of mononuclear cell infiltration (MNCI) (0, no infiltration; 1, <25%; 2, 25–50%; 3, 50–75%; 4, >75%); segmental distribution of MNCI (0, continuous; 1, mildly segmental; 2, markedly segmental); and eosinophil infiltration (0, none or minimal; 1, mild; 2, severe).…”
Section: Methodsmentioning
confidence: 99%
“…50,51 Antineutrophil cytoplasmic antibody (ANCA) 52 A meta-analysis showed the risk of chronic pouchitis was higher in ANCA-positive patients, but the risk of acute pouchitis was unaffected by ANCA status. 52 Histologic findings of colectomy samples 53 The combination of the degree of mononuclear cell infiltration (MNCI), segmental distribution of MNCI, and eosinophil infiltration in the resected total colon had a utility to predict the development of chronic pouchitis. 53 3-Stage ileal pouch-anal anastomosis (IPAA) 54 A multicenter, retrospective cohort study of pouchitis in pediatric ulcerative colitis showed that 3-stage IPAA may increase the risk of pouchitis.…”
Section: Factors Commentsmentioning
confidence: 99%
“…52 Histologic findings of colectomy samples 53 The combination of the degree of mononuclear cell infiltration (MNCI), segmental distribution of MNCI, and eosinophil infiltration in the resected total colon had a utility to predict the development of chronic pouchitis. 53 3-Stage ileal pouch-anal anastomosis (IPAA) 54 A multicenter, retrospective cohort study of pouchitis in pediatric ulcerative colitis showed that 3-stage IPAA may increase the risk of pouchitis. 54 Nonsteroidal anti-inflammatory drugs (NSAIDs) 46,49 NSAIDs was reported to increase the risk of pouchitis.…”
Section: Factors Commentsmentioning
confidence: 99%
See 1 more Smart Citation